Commons Dilemma pada Pengelolaan Daerah Irigasi Kapilaler, Kabupaten Klaten - Wahyu Indriastuti; Mohammad Muktiali (Jurnal Wilayah dan Lingkungan, 2015)
Water resource is a part of common pool resources. In the management, common pool resources are faced with triggered conflicts between stakeholders because the resource characteristics are freely used by everyone, but its useful will be decreased. The implication of this problem raises a phenomenon called commons dilemma. It is happened when the management of common pool resources and its consequences is faced with the weakness of institutional aspect. This phenomenon also happened on the research object that is Kapilaler Irrigation Area. The research applies a qualitative approach with case study strategy research. The analysis technique is descriptive qualitative analysis. The research finds that commons dilemma in the management of Kapilaler Irrigation Area is a condition when the water resources management dealt with the weakness of cooperation between stakeholders so that it produces negative impact to the resources and rivalry between the users. This research also shows that the sufficiency of resource condition is not assured all successfully of resource management while the institutional aspect remains weak.